Women Workers In The Qur'an (A Study of Maqasidi Interpretation Approach) : (STUDI PENDEKATAN TAFSIR MAQÄ€á¹¢IDI) - Solehah, Naimmatus; Irsad, Muhammad; Prasetiawati, Eka (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2024)
Developments from time to time affect significant changes in women, one of which is their position in society to get a job. Such women are called working women. This study examines women workers in the Qur'an using the thematic method and maqÄá¹£idi interpretation as its approach. This research focuses on Q.S al-Qaá¹£aá¹£ [28] : 23 and Q.S al-Aá¸¥zÄb [33] : This research is a literature review with the primary sources of tafsir al-Qurthubi, tafsir JalÄlain, and tafsir al-Munir. The conclusion of this study indicates that the verse describes the permissibility of women working as long as they maintain their honor. In addition, women are also not allowed to be excessive in adornment. While from the findings regarding the aspects of maqÄá¹£id al-syarÄ«'ah and the fundamental values of the Qur'an, the author finds a prominent aspect which is hifdzu nafs, because in this verse it is explained that the two women protect themselves from being crowded with other herders by waiting for the herders to finish at the water source, there is also a value of equality that stands out because it shows the equal position between men and women in terms of work. If contextualized in this day and age, women are allowed to work to fill their spare time and develop their skills. The wisdom that can be learned is that women can utilize their time by doing useful work, and work to meet their needs as long as they pay attention to the conditions when working.